PENGARUH KONTRAK HUTANG, BIAYA POLITIK, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA PADA SEKTOR INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA TAHUN 2016-2018 - Venina, Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to know the effect of leverage, political cost, and institutional ownership of earnings management on manufacturing company listed on the Indonesia Stock Exchange from 2016-2018. The sampling method used in this research used 36 manufacturing companies that were selected using purposive sampling method. Data used for this studyis obtained from financial statement for the year ended December 31st during 2016-2018. Analysis tool that will be used to analyze the hypothesis with multiple linier regression model is software Eviews 9.0. The result for this research showed that leverage have negative and not significant effect, political cost have positive and not significant effect, while institutional ownership have positive and significant effect.